Transformasi Digital dalam Akuntansi: Dampak Teknologi Blockchain terhadap Transparansi dan Keamanan Laporan Keuangan - Dwi Ayu Destiani; Khoerunnisa Khoerunnisa; Ira Fadila; Dien Noviany Rahmatika (JOURNAL OF SHARIA ECONOMICS, 2025)
The rapid development of digital technology has transformed the accounting field, encouraging organizations to adopt systems that ensure higher levels of transparency, security, and reliability in financial reporting. Blockchain has emerged as one of the most influential technologies due to its decentralized architecture and immutable ledger. This study aims to synthesize current research findings regarding the impact of blockchain technology on the transparency and security of financial statements through a Systematic Literature Review (SLR) approach. The results of this study show that blockchain, enhances the accountability of financial information by providing permanent, traceable, and encrypted transaction records that reduce fraud risk and human error. In addition, blockchain strengthens data security through cryptographic validation and distributed storage mechanisms that protect financial information from manipulation and unauthorized access. However, the literature also highlights several implementation challenges, including regulatory uncertainty, limited organizational readiness, low digital literacy, and scalability issues. Overall, this study concludes that blockchain presents significant opportunities to improve the quality, trustworthiness, and resilience of financial reporting systems, although effective implementation requires adequate regulatory support, human resource development, and technological infrastructure.